Beyond the Uniform: Determinants of Income and Welfare Among Indonesian Navy Retirees - Suwarno, Panji; Triyani, Triyani; Sindrawati, Sindrawati (Jurnal Manajemen Pelayanan Publik, 2025)
Retirement among Indonesian Navy personnel often creates a sharp decline in income while financial needs persist, underscoring the urgency to identify determinants of post-service welfare. This study aims to examine how education, training, occupation, age, and rank shape income and welfare among Navy retirees. Drawing on human capital and empowerment theory, it employs a quantitative explanatory design with purposive sampling of 202 respondents in East Java. Data were collected using structured questionnaires and analyzed with Partial Least Squares–SEM via SmartPLS 4.1.0.0, complemented by multiple regression analysis. Results indicate that education has the strongest effect on welfare, training enhances income, and rank significantly predicts income disparities, while post-service occupation contributes positively to welfare. However, the model explains welfare and income only moderately, implying the role of other structural and social factors. These findings highlight the importance of comprehensive empowerment strategies that combine individual capacity building with institutional support.